2016
DOI: 10.1021/acs.jpca.6b06146
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Green Fabrication of a Superhydrophobic Surface by One-Step Immersion for Continuous Oil/Water Separation

Abstract: In this paper, stainless steel meshes with superhydrophobic and superoleophilic surfaces were fabricated by rapid and simple one-step immersion in a solution containing hydrochloric acid and stearic acid. The apparent contact angles were tested by a video contact angle measurement system (CA). Field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS) were conducted to characterize the surface topographies and chemical compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Both -CH 3 and -CH 2 - are hydrophobic groups and have low surface energy decreasing the surface energy of the surface they cover or of the materials they are grafted to [ 35 , 36 ]. The free -COOH band of solid stearic acid is still present in the spectrum of the as-deposited StMAPLE(266 nm) film while it vanishes in the spectrum of the film after 36 months of storage, which shows that the stearic acid had reacted with the Si surface, although there are no changes in contact angle value [ 37 , 38 ]. It has been observed that an “ordered” film of alkanoic acids is characterized by alkyl chains in all-trans configurations arranged in such a way that they are tilted from the normal surface at the same angle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both -CH 3 and -CH 2 - are hydrophobic groups and have low surface energy decreasing the surface energy of the surface they cover or of the materials they are grafted to [ 35 , 36 ]. The free -COOH band of solid stearic acid is still present in the spectrum of the as-deposited StMAPLE(266 nm) film while it vanishes in the spectrum of the film after 36 months of storage, which shows that the stearic acid had reacted with the Si surface, although there are no changes in contact angle value [ 37 , 38 ]. It has been observed that an “ordered” film of alkanoic acids is characterized by alkyl chains in all-trans configurations arranged in such a way that they are tilted from the normal surface at the same angle.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that an “ordered” film of alkanoic acids is characterized by alkyl chains in all-trans configurations arranged in such a way that they are tilted from the normal surface at the same angle. This results in νCH 2 -asymmetric ≤ 2916 cm −1 [ 37 , 38 ]. Table 3 includes a column with the position of this peak.…”
Section: Resultsmentioning
confidence: 99%
“…Changing the wetting properties of the material surface changes the selective adsorption of water-oil. A variety of oil-adsorbing and hydrophobic materials for oil-water separation have been prepared and encouraging results were obtained [10][11][12]. In addition, there are many 3D porous materials with hydrophobic and oil adsorption capacity that have been successfully applied to oil-water separation, but their practical applications are still limited by complex preparation methods and high raw material costs [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Both low surface energy and rough surface structures are the main inuencing factors of superhydrophobicity. 12,13 Various ltration materials with superhydrophobicity and superoleophilicity, such as textiles, 14 meshes, 15 cellulose sponges, 16 and membranes, 17 have been fabricated to selectively lter water or oil from oil/water mixtures. Among articial superhydrophobic materials, [18][19][20][21][22] as-prepared mesh surfaces with superhydrophobic character have been some of the most promising examples owing to their strong water repellence, which endowed hierarchical surfaces with robust superhydrophobicity and uses in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that the preparation process via one-step immersion is convenient and simple. 15 In this article, a superhydrophobic and superoleophilic mesh with hierarchical micro/nanostructures was fabricated via a green, rapid, and highly effective electrodeposition process and chemical modication with PDMS. The porous coated mesh retained excellent superhydrophobicity aer immersion in solutions of different pH values and abrasion cycling tests.…”
Section: Introductionmentioning
confidence: 99%